Time on task for collaborative augmented reality in science experiment - Matcha, W. (Penerbit UTM Press, 2016)
This paper reports on a study findings on the time participants spend engaged doing task while interacting with Augmented Reality (AR) based system in collaborative learning environment. Engaged time is an important factor in any learning approaches as it is the actual time that participants pay attention and acquire knowledge. In the present study, time-on task and time off task were used to investigate the student level of engagement in learning activities. Data was collected from an observation study using video recording approach. Result showed that participants spend more than ninety percent concentrating on task related activities. Result from a survey questionnaire following the study revealed that participants enjoy group learning using AR as a tool. These findings further indicate that fun learning environment offered by augmented reality technology has the potential to grab learnerâs attention and motivate them to stay focus on the learning activities. Â© 2016 Penerbit UTM Press. All rights reserved